What Is in a Natural Resource Management Plan? - Chris Demers; Robert Clausen (EDIS)
This document outlines the essential components of a natural resource management plan for forest properties. It emphasizes the importance of clear objectives, property location and history, resource assessment, management recommendations, and an activity schedule. The plan serves as a “road map” to guide landowners in achieving their desired outcomes, such as timber production and wildlife habitat improvement. It also highlights the role of consulting foresters and the need for periodic reviews to adapt to changing conditions. The document provides practical advice for creating a flexible and effective management plan. First published August 2001.